Effectiveness of interventions to promote physical activity in overweight adults in the health care setting : a systematic review - Nuojua, Sohvi Katariina (2017)
Overweight and obese individuals are at a significant risk for developing cardiovascular disease and other health concerns. Increasing physical activity (PA) in this population is associated with weight loss and positive health outcomes. One way of promoting PA is through interventions in the health care setting. Research is needed to identify the most effective ways of motivating overweight individuals to increase their PA behaviour and to maintain these changes. This systematic review seeks to synthesise current evidence on the effectiveness of behavioural interventions aimed at increasing PA in the overweight and obese population in the health care setting. Literature searches were performed to locate RCT behavioural interventions with follow-up data, targeting PA in healthy overweight and obese adults (BMI>25) in health care settings. Two rounds of literature search were done in electronic databases for MEDLINE, EMBASE, CINAHL, CCRCT, and PsycINFO in spring 2015 and 2017. 11 primary studies were identified. The included studies were evaluated for risk of bias. Data extracted included participant characteristics, results on PA, behaviour change techniques (BCTs) and theoretical frameworks used, and properties of intervention delivery. The BCTs used were coded by two independent assessors using the Behaviour Change Taxonomy version 1. Qualitative synthesis was determined as the most suitable method for reporting the summative data. Most studies were rated as being at low risk of bias. Majority of the studies reported significant time-effects that were rarely maintained at follow-up. Significant increases in PA that favoured the experimental condition were identified in three studies. No superiority of individual BCTs was identified, although self-monitoring was frequently used by successful studies. There was no indication of any intervention delivery properties being associated with intervention success. The limitations of the review include heterogeneity and risk of bias within the study pool, as well as lack of interrater communication. The qualitative synthesis cannot provide enough information for a conclusion to be made yet on the effectiveness of specific BCTs in motivating the overweight and obese population to increase their PA behaviour. The only recommendation for guiding practice is that self-monitoring may be an effective technique for increasing PA in the health care environment, albeit this recommendation is based on weak evidence. Future RCTs should ensure high methodological quality and adequate reporting of BCTs used so that they can contribute to prospective systematic reviews and provide stronger evidence for guiding practice in the health care setting.